The first molecular identification of benzimidazole resistance in Haemonchus contortus from goats in Thailand - Pitaksakulrat, Opal (Vet World, 2021)
BACKGROUND AND AIM: Haemonchus contortus is one of the major trichostrongyloid nematodes affecting small ruminant production worldwide, especially in tropical and subtropical regions. Adult H. contortus suck the blood from the host abomasum leading to anemia and often death in heavily infected animals. The mainstay of parasitic control is an anthelmintic drug, but long-term drug use may cause drug resistance. The aim of this study was to examine benzimidazole resistance in H. contortus of goats from different regions in Thailand by detecting the frequency of the F200Y polymorphism in the β-tubulin isotype 1 gene. MATERIALS AND METHODS: A total of 121 H. contortus adults were obtained from 31 naturally infected out of 37 slaughtered goats from city abattoirs in five regions of Thailand. The frequency of the F200Y polymorphism in the β-tubulin isotype 1 gene was detected following the allele-specific polymerase chain reaction protocol. RESULTS: The overall genotype frequencies in Thailand were homozygous resistant (RR: 24%), heterozygous (SR: 44.6%), and homozygous susceptible (SS: 31.4%). The allele frequencies were resistant allele (R: 46%) and susceptible allele (S: 54%). The R allele frequency and the RR genotype varied from 30% to 65% and 0% to 43.9%, respectively. The frequency of R alleles was significantly higher in the southern region (0.65) as compared to northern (0.30, p=0.001), western (0.38, p=0.04), and central regions (0.30, p=0.03). The RR genotype was also significantly higher in the southern region (43.9%) versus the northern (0 %, p=0.001), western (11.8%, p=0.012), and central regions (17.4%, p=0.001). CONCLUSION: This is the first study of the detection of single-nucleotide polymorphisms in codon 200 of the β-tubulin isotype 1 gene of H. contortus from goats in Thailand. These findings are essential and imply that an integrated approach is needed for issues such as drug treatment, farm management, prevention, and control strategies. This is of interest to farmers, veterinarians, and the department of livestock.